The effect of local environment on innovation: a comparison of local and foreign firms in China. (2018) - Li, Peng-Yu; Huang, Kuo-Feng; Xu, Kai; Yu, Chwo-Ming Joseph
Innovative activities have become increasingly important to firms in emerging markets, particularly in China in recent years. Facing weak institutional and competitive environments in China, firms building local connections to react and to innovate can hold a better competitive position. Our study investigates how building local connections and local competition may influence a firm's innovation and compares the moderating effect of ownership (local vs. foreign firms) on firm innovation in the early 2000s. Our empirical findings suggest that, in China, local connections are conducive to firm innovations. Compared with local firms, foreign firms tend to have more innovations. However, when facing severe local competition, local firms are engaged in more innovative activities than foreign firms. We suggest the advantages of local connection owned by local companies may outperform the foreign companies. The foreign companies need to adapt their strategies to succeed in the fast changing emerging market.